Techno-Economic Analysis and Optimisation of Campus Grid-Connected Hybrid Renewable Energy System Using HOMER Grid - Riayatsyah T.M.I.; Geumpana T.A.; Rizwanul Fattah I.M.; Rizal S.; Indra Mahlia T.M. (MDPI, 2023)
alternative energy; electricity; emission control; energy storage; methodology; mitigation; optimization; photovoltaic system; simulation; software; technical efficiency; wind turbine; Greater Sunda Islands; Sumatra; Sunda Isles